Pengembangan Perangkat Pembelajaran Pembuktian dengan Strategi Abduktif-Deduktif untuk Meningkatkan Kemampuan Geometri Siswa SMA - Ernawati Ernawati; M. Ikhsan; Saminan Saminan (Jurnal Peluang, 2019)
Until now student mastery of the material geometry is still relatively low. Many difficulties experienced by students in understanding the geometry of the material, one of which is the difficulty in proving. In addition, the study is not yet available devices that can specifically serve the needs of teachers in the teaching of mathematical proof. Therefore, it is necessary to develop learning tools of proof that can help teachers and train students in the proof of the geometry in school. In this study the evidence used strategy is the strategy of abductive-Deductive. This study aims to develop and produce learning device geometry proof. This type of research is the development of research refers to the model of Plomp through four stages, namely a preliminary investigation stage, the design stage, the stage of realization / construction, and stage of the test, evaluation and revision. This research trials in SMA Laboratorium Unsyiah Banda Aceh. The research showed the average score validator for RPP 4.52, 4.58 LKPD, teaching materials and test 4.54 4.30 learning outcomes, adherence to the 91%, the average score of 3.73 practicality test, 86% students with a positive response, and 80.7% of students complete. This shows that the learning device valid criteria, practical and effective way to improve the geometry of high school students.